2009
DOI: 10.1021/ic802220w
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and in vitro Antimalarial and Antitumor Activity of New Ruthenium(II) Complexes of Chloroquine

Abstract: The new RuII chloroquine complexes [Ru(η6-arene)(CQ)Cl2] (CQ = chloroquine; arene = p-cymene 1, benzene 2), [Ru(η6-p-cymene)(CQ)(H2O)2][BF4]2 (3), [Ru(η6-p-cymene)(CQ)(en)][PF6]2 (en = ethylenediamine) (4), and [Ru(η6-p-cymene)(η6-CQDP)][BF4]2 (5, CQDP = chloroquine diphosphate) have been synthesized and characterized by use of a combination of NMR and FTIR spectroscopy with DFT calculations. Each complex is formed as a single coordination isomer: in compounds 1–4 chloroquine binds to ruthenium in the η1-N mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
130
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(146 citation statements)
references
References 62 publications
15
130
1
Order By: Relevance
“…Of note, Sánchez-Delgado and co-workers reported the preparation of ruthenium half-sandwich analogues of CQ which were found to be highly potent and to overcome the CQ resistance. 28 Organometallic compounds have also been investigated for their activity against other parasites such as the trypanosome Trypanosoma cruzi (T. cruzi) or Echinococcus multilocularis metacestodes. [29][30][31] For example, a ruthenium halfsandwich complex of the antifungal drug clotrimazole was found to be 58 times more potent than the parent drug in vitro against T. cruzi.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, Sánchez-Delgado and co-workers reported the preparation of ruthenium half-sandwich analogues of CQ which were found to be highly potent and to overcome the CQ resistance. 28 Organometallic compounds have also been investigated for their activity against other parasites such as the trypanosome Trypanosoma cruzi (T. cruzi) or Echinococcus multilocularis metacestodes. [29][30][31] For example, a ruthenium halfsandwich complex of the antifungal drug clotrimazole was found to be 58 times more potent than the parent drug in vitro against T. cruzi.…”
Section: Introductionmentioning
confidence: 99%
“…4) in this series exhibited IC 50 values in the range of 234-906 nM against CQ-R strains. However, the hybrid molecules were less active than CQDP against most CQ-S strains, except the 3D7 CQ-S strain (Rajapakse et al, 2009a). Certain platinum-based organometallic and 4-aminoquinoline hybrids (e.g., 13 in Fig.…”
Section: Learning From the Cq Hybrid Approach For Antimalarial Drug Dmentioning
confidence: 99%
“…However, they showed low therapeutic index for antimalarial activity due to high cytotoxicity . Rajapakse et al (2009a) reported that the transition metal ruthenium (II) and CQ hybrids possess antimalarial and anticancer activities with good solubility. In addition, the presence of an arene ring in these compounds increase lipophilicity by stabilizing the metal center.…”
Section: Learning From the Cq Hybrid Approach For Antimalarial Drug Dmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction of FQ and CQ against P. falciparum strains is quite unique and different in which FQ reveal some high potency in chloroquine-resistant and chloroquine-sensitive P. falciparum strains [26][27][28][29][30][31][32].…”
Section: R1=r2 = H X = Clmentioning
confidence: 99%